Three-dimensional floating display system - Li, Yuchen (Nanyang Technological University, 2020)
In nowadays, there was a lot of applications such as three-dimensional visual entertainment, three-dimensional medical production, virtual reality entertainment which use three-dimensional image processing technology. These popular applications proved that three-dimensional display technology is an attractive topic for research. However, the previous technology still had a lot of aspects to be improved, such as image distortion, settled view position and three-dimensional glasses. Three-dimensional display system without wearing special three-dimensional glasses is an attractive topic nowadays. In this project, one three-dimensional image display system has been studied and a 3d image floating display system was demonstrated. In first part of this project, it introduce a lens array image construction system and a 3d display system called an eye-tracked laser based 3D display. In the eye-track laser based 3D display system, the main part consists of one scanning laser, one ferroelectric liquid crystal spatial light modulator (FLC-SLM) array and a transmission screen. In this system, the scanning laser backlight is modulated by the FLC-SLM array to produce directional backlight. By employing eye-track technology and time-sequential method, the directional backlight is projected on the location of viewers’ eye in real time, which viewers are able to move freely. The second system is called floating display 3d image system, which consist of an LCD light source, one polarizing filter system and one special glass plate. The direction of the backlight of LED will be transmitted through the polarizing filters form a directional light. After that, the special glass plate will collect that light on this side and create an image identical to the original at the same distance on the other side.